Bank Concentration: An Analysis of Public Sector Banks in India - Dhawan, Shivam; Niharika (Gyan Management Journal, 2019)
Research evidence has substantiated that consolidation in banking sector through mergers and amalgamations is responsible for concentrated banking structure in India, where public sector commercial banks dictate the Indian banking sector in terms of its market share. In this context, the present research study endeavors to assess the bank concentration byHerfindahl-Hirschman Index (HHI) in terms of total assets for all the public sector commercial banks in India for a ten year time period from 2008 to 2017.The research study also aims to analyze whether or not the bank concentration has shown growth during the said time period. The results indicated that State Bank of India has recorded the highest average market share in terms of total assets amongst all the public sector banks in India followed by Bank of Baroda, whereas State Bank of Mysore has registered the lowest average market share in terms of total assets. The trend analysis further revealed that even though the overall average HHI value (0.090) has been low for the said time period, butbank concentration in terms of total assets has increased amongst all the public sector banks of India as revealed by the positive growth percentage of HHI (20.22%) during the said time period.